FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR PESERTA DIDIK KELAS XI SMA NEGERI 11 PADANG - Rahayu, Winda; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The problem in this study is how the factors that influence the motivation of learners in class XI SMA Negeri 11 Padang. This study aimed to describe: (1) internal factors that affect the motivation of learners in class XI SMA 11 Padang (2) external factors that affect the motivation of learners in class XI SMA Negeri 11 Padang. This research is a descriptive study sought to describe a situation for what it is. The populations in this study were students at SMAN 11 Padang, with a number of 162 learners. Sampling in this study using simple random sampling is sampling at random from the population members in the members of the population, where the sample size is 32 people. As for the use of data analysis techniques percentage. RESULTS: (1) Internal factors that affect the motivation of learners in class XI SMA Negeri 11 Padang is in the category that is much less on the criteria of 65.62%, (2) external factors that affect the motivation of learners in class XI SMA Negeri 11 Padang is in many categories, namely at 62.65% criteria. Based on the research findings recommended for learners to be able to increase the motivation to learn. Research findings recommended to the principal and teachers at 11 high schools in Padang to help motivate learners.